Determinasi Faktor Yang Mempengaruhi Indeks Pembangunan Manusia Provinsi Jawa Barat Tahun 2015 - 2019 - Adam Wahyu Setiawan, (2021)
The Human Development Index of an area is very helpful in supporting national development, such as a comparative measurement of life expectancy, education, health and living standards for all countries. however, not all regions have an even Human Development Index. This is thought to be due to a gap in government spending and poverty, therefore in this study discusses the determinants of the Human Development Index determined by Poverty, Government Expenditures in the Education Sector, Government Expenditures in the Health Sector, while the results show that Poverty and Government Expenditure Regional health is proven to have an effect on the Human Development Index because Poverty is one of the determining factors that play a major role in the Human Development Index, as well as Government Expenditure on the Health Sector which is also one of the determinants of the Human Development Index. Furthermore, the Government Expenditure on the Education Sector which is proven to have no effect on the Human Development Index is low in the support of limited funding sources. These limited sources of funds have resulted in relatively low government spending in the education sector to finance the public sector.